NVH Analysis and Performance Optimization of Drive Bridge based on Load Transmission Error - Nie Shaowu; Huang Juhua; Lai Changfa; Tang Sicheng; Yang Jianjun; Xu Yong (Jixie chuandong)
In order to improve NVH performance of drive bridge，from the aspect of transmission error，a method of drive bridge NVH analysis and performance optimization is established based on actual working conditions. Firstly，the exactly model of drive bridge is established based on MASTA software，and the gear meshing misalignments are calculated according to the actual load. Secondly，the change law of load contact area and load transmission error is obtained by TCA and LTCA analysis for drive bridge gear based on the actual working conditions. On this basis，the NVH simulation and analysis method for drive bridge is studied based on the MASTA software，and the drive bridge noise curve under the actual working conditions is obtained. Finally，the influence relation between the load transmission error and drive bridge noise curve is established，and the drive bridge NVH performance is optimized by controlling the transmission error. The theoretical guidance for vibration and noise reduction of drive bridge and modification and optimization of main reducer gear are provided.